Keberlangsungan Ojek Konvensional - Lindiwatie, Lindiawatie; Ghafar, Abdul (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2018)
Technological advances in the field of application-based ride service through smart mobile phones have caused rejection from conventional motorcycle ride service community. Based on the phenomenon, this research aims to find out the survival efforts from conventional motorcycle transportation service against app-based ride service through its management and services. The research method applied in this study was qualitative method using observation, structured interviews and documentation. The result of the study shows that conventional motorcycle tranportation is a non-professional service with minimal knowledge, making it unreliable. Thus, the effort taken to survive is in form of organization's management based on family values of harmony, solidarity and mutual cooperation. In fact, the conventional motorcycle transportation powerless action facing the competition with the app-based or online transportation service is not balanced. Aware of the situation, it is necessary for government to create policies and rules that guarantee the livelihood of its citizens and also for online motorcycle transportation companies’ stakeholders though the Corporate Social Responsibility (CSR) activities to embrace the conventional motorcycle transportation riders to be able to embody the values of social economic resilience in the community.